Chronic Disseminated Histoplasmosis in a Young Immunocompetant Patient of Hypobetalipoproteinemia: A rare Presentation - Gupta, Rakesh Kumar; Batra, Vineeta Vijay; Sakhuja, Puja; Dahale, Amol; Puri, Amarender Singh (Annals of Pathology and Laboratory Medicine, 2015)
Disseminated histoplasmosis is commonly found in immunocompromised patients in association with acquired immunodeficiency syndrome in endemic regions but is rare in other parts of the world. We herein describe a case of subacute disseminated histoplasmosis in a young 20-year-old lady presenting with the chief complaints of pyrexia of unknown origin, loose stools and generalized body swelling with a previous diagnosis of hypobetalipoproteinemia. Supraclavicular lymph node, bone marrow aspiration and colonic biopsy revealed numerous yeast forms of fungus histoplasma. This case illustrates that DH should be ruled out in immunocompetent non-endemic patients presenting with chronic fever even in the absence of respiratory symptoms.Â